Studi Docking Molekular Aktivitas Panghambatan Enzim Tirosinase Ubi Jalar (Ipomoea batatas L. Lam) - Dwi Utami; Ryan Syahputra; Wahyu Widyaningsih (Universitas Muhammadiyah Surakarta, 2022)
Sweet potato (Ipomoea batatas L. Lam) is a plant source of carbohydrates with chemical content of catechins, quercetin, asam klorogenat, anthocyanins, beta-carotene. These phytochemical compounds have been shown to have antioxidant activity that is closely related to tyrosinase through the oxidative stress pathway. The purpose of this study was to develop sweet potato plants as anti-tyrosinase candidates for cosmetic preparations by molecular docking of these 4 compounds to tyrosinase protein (pdb:2Y9X) with kojic acid control. The research was done in 4 stages : (1) Preparation of proteins (receptors) and ligands with Biovia Discovery Studio (2) Optimization of geometry with Avogadro and Chem 3D (3) Validation of docking and molecular docking methods for proteins (2Y9X) with Autodock-4 (5) and (4) ADMET study with pkCSM and SwissADME websites. The test results obtained the highest affinity for 3 active compounds, namely beta-carotene with (ΔG) -6.05 kcal/mol (IC) 36.72 M and quercetin has (ΔG) -5.87 kcal/mol (IC) 45.30 M . While the control kojic acid has a lower affinity of (ΔG) -5.27 kcal/mol (IC) 380.37 M. ADMET predictions provide information that the four active compounds Ipomoea batatas L. Lam meet the requirements to be developed as natural tyrosinase inhibitors based on lipophilicity (logP), topology polar surface area (TPSA), skin permeability, skin sensitivity, logKP, CYP1A2 inhibitor, lipinski rule. and bioavailability. The molecular docking study and ADMET prediction indicate that the active compound of sweet potato (Ipomoea batatas L. Lam) has the potential to be developed as a natural cosmetic ingredient.